Secondary syphilis: diagnostic madeby oral lesions - Noronha, Augusto César C; Israel, Mônica S; Almeida, Daniel CF; Moreira, Gisele M; Lourenço, Simone QC; Dias, Eliane P (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the syphilis is a infectious and contagious illness that is ascending in the Brazilian public health scenario. All professionals of the health areamust be aware of the manifestations of this illness and the possibility of injuries made by the desease, also oral manifestations. Objective: to analize a clinicalcase of sífilis that was diagnosised from injuries in the oral cavity. Methods: clinical and histopatologic analysis of the injuries of the patient have been made,as well as examinations in laboratories (VDRL). Results: the association of the histopatologic findings with the positive result of the VDRL, confirmed thediagnostic hypothesised of sífilis. Conclusion: the knowledge of the manifestations of the syphilis in all its period of training for health professionals is ofbasic importance, so that they are able to execute a correct diagnosis and treatment.